National Consultation on Justice Issues: Dominica - (:unkn) unknown (My University, 2016)
The consultation was held in Dominica on January 29th and 30th, 2001. The Project Advisory Committee (PAC) commenced preparations for the consultation inDecember 2001. It was decided to alter the format of the proceedings for the consultationand to invite participants to pre register indicating their preferences for discussiongroups. The event included presentations on topics like legal aid, alternative dispute resolution, mediation, restorative justice, etc.